ChemInform Abstract: Copper‐Catalyst‐Controlled Site‐Selective Allenylation of Ketones and Aldehydes with Propargyl Boronates. Issue 29 (1st July 2013) - Fandrick, Keith R.; et al., et al.
Abstract The substitution pattern both on the copper‐catalyst ligand and on the propargyl boronate are crucial for the site selectivity of the reaction.